The Obligation of Husband to Provide Financial Support in IslamicFamily Law Perspective toward a Financially Independent Wife - Fauzi, Ahmad; Choeri, Imron; Hudi, Hudi (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The increasing participation of wives in income-generating activities has become a significant feature of contemporary family life, reshaping economic relations within households and raising important normative questions regarding financial responsibility. Within the framework of Islamic family law, the obligation of financial maintenance (nafkah) remains a fundamental and binding duty of the husband toward his wife and children, as firmly established in the Qur’an, the Sunnah, and the Compilation of Islamic Law (KHI). However, modern socio-economic realities increasingly reflect shared economic roles between spouses, particularly in families where wives earn independent income. This study examines the legal construction of the husband’s obligation of nafkah and analyzes its relevance in the context of working wives with independent earnings. Employing a library-based research method, the study adopts a normative-theological and descriptive-analytical approach. The analysis draws upon classical Islamic jurisprudential sources, contemporary scholarly literature, and relevant legal regulations, which are examined through the principles of justice, reciprocity, and family responsibility in Islamic law. The findings indicate that the husband’s obligation to provide nafkah remains legally binding regardless of the wife’s economic status. The wife’s income is recognized as her exclusive personal right and does not invalidate the husband’s responsibility, although it may be voluntarily allocated to support household needs. Consequently, Islamic family law accommodates economic transformation while preserving its normative foundations, encouraging balanced and harmonious partnerships within modern Muslim families.